Marketing strategy for tourist attractions to increase intention to visits Pura Taman Ayun, Bali - Meirejeki, I Nyoman; Pemayun, I Dewa Gede Ari; Santanu, Gede; Jaya, I Made Sura Ambara; Kanca, I Nyoman (International research journal of management, IT and social sciences, 2023)
Tourist attraction Taman Ayun is a tourist place on the island of Bali which is located in the village of Taman Ayun, District Abiansemal, Badung, Bali Province. The tourist attraction Taman Ayun is present in the form of long tail macaques, Pala Forest, and Pura Bukit Sari as its appeal. The number of tourists who visited Travel Attractions Taman Ayun from time to time experienced an increase after falling dramatically in 2012, amounting to 54 637 people, but the increase in the number of tourists is still quite slow and when compared with the visit of the peak that occurred in 2009 amounted to 225 672 people is still very low. The research aims to the right marketing strategic to increase rapidly tourists to visit Taman Ayun Travel Attractions. The method used in this study is through questionnaires, observation, library research, documentation, and interviews with the manager. The data obtained were analyzed using descriptive analysis techniques were used to analyze the marketing mix and strategy using SWOT analysis as well as using a Likert scale to analyze the questionnaires that were distributed.